fNIRS Evaluation of Frontal and Temporal Cortex Activation by Verbal Fluency Task and High-Level Cognition Task for Detecting Anxiety and Depression - Lang, Xuenan; Wen, Dan; Li, Qiqi; Yin, Qin; Wang, Mingyu; Xu, Yong (Frontiers in Psychiatry, 2021)
anxiety and depression are wide-spread psychosis which are believed to affect cerebral metabolism, especially in frontal and temporal cortex. The comorbidity patients of anxiety and depression(A&D) have more serious clinical symptoms. Functional near-infrared spectroscopy (fNIRS) is a noninvasive modality to monitor the human brain oxygenation, and it could be considered as a potential tool to detect psychosis which may lead to abnormal cerebral oxygen status when the brain is activated. However, how sensitive the cerebral oxygenation response to the cortex activation and whether these responses are consistent at different stages of A&D or different regions, still remains unclear. In this study, a conventional physiological paradigm for cortex activation, i.e., verbal fluency task (VFT), and a relative new paradigm, i.e., high-level cognition task (HCT), were compared to detect A&D through longitudinal measurement of cerebral oxygen status by fNIRS. The A&D patients at acute, consolidation and maintenance stages, as well as the healthy subjects participated in VFT and HCT paradigm respectively. For most of subjects, the oxy-Hb is found to increase remarkably, accompanied with relatively small reduction in deoxy-Hb when subject to both paradigms. The statistical analyses show a relatively large variability within any group, leading to the significant difference was only found between A&D at acute-stage and healthy subjects in temporal lobe region(p<0.001). Nevertheless, HCT would activate more oxygen increment when compared with the VFT, with a large integral value in oxy-Hb. On average, the oxy-Hb integral value of the A&D patients differ substantially at different stages when subject to HCT paradigm. Moreover, prefrontal lobe and temporal lobe responses more consistently to the HCT paradigm rather than the VFT paradigm. Under the VFT paradigm, however, no remarkable difference in integral value was found among the three stages, either at prefrontal lobe or at temporal lobe. This study indicated that HCT, which is intensively involved in brain function, would activate more oxygenation change in cerebral cortex. Additionally, with good performance at distinguishing different stages according to oxy-Hb criterion, the HCT has the potential to evaluate the therapeutic effects for A&D patients.